Immunogenicity and Safety of a Quadrivalent Meningococcal Conjugate Vaccine Versus Nimenrix in Healthy Adolescents: A Randomized Phase IIIb Multicenter Study - Javier Díez-Domingo; Róbert Simkó; Giancarlo Icardi; Chan Poh Chong; Céline Zocchetti; Olga Syrkina; Siham Bchir; Isabelle Bertrand-Gerentes (Infectious Diseases and Therapy)
Abstract Introduction Many immunization programs in Europe recommend quadrivalent meningococcal vaccinations, which are often administered concomitantly with other vaccines. We compared the immune response of a tetanus toxoid conjugated quadrivalent meningococcal vaccine (MenACYW-TT, MenQuadfi®) with another quadrivalent meningococcal conjugate vaccine (MCV4-TT; Nimenrix®) when administered alone or concomitantly with Tdap-IPV and 9vHPV vaccines in adolescents. Methods In this phase IIIb trial, healthy adolescents (MenC-naïve or MenC-primed before 2 years of age) from Spain, Italy, Hungary, and Singapore were randomized in a 3:3:2 ratio to receive either MenACYW-TT or MCV4-TT alone, or MenACYW-TT concomitantly with 9vHPV and Tdap-IPV. The primary objective was to demonstrate the non-inferiority of the seroprotection rate (human serum bactericidal assay [hSBA] titer ≥ 1:8) to serogroups A, C, W, and Y 30 days post-vaccination with a single dose of MenACYW-TT or MCV4-TT. Secondary objectives included describing hSBA titers for the four serogroups before and 1 month following vaccination and according to MenC priming status. Results A total of 463 participants were enrolled (MenACYW-TT, n = 173; MCV4-TT, n = 173; MenACYW-TT/9vHPV/Tdap-IPV n = 117). Non-inferiority based on seroprotection was demonstrated for MenACYW-TT versus MCV4-TT for all serogroups. Immune responses were comparable whether MenACYW-TT was administered alone or concomitantly with Tdap-IPV and 9vHPV. Post-vaccination hSBA GMTs were higher in MenACYW-TT vs. MCV4-TT for serogroups C, Y, and W and comparable for serogroup A. The percentages of participants with an hSBA vaccine seroresponse were higher in MenACYW-TT vs. MCV4-TT for all serogroups. For serogroup C, higher GMTs were observed in both MenC-naïve or -primed participants vaccinated with MenACYW-TT vs. MCV4-TT. Seroprotection and seroresponse were higher in MenC-naïve participants vaccinated with MenACYW-TT vs. MCV4-TT and comparable in MenC-primed. The safety profiles were comparable between groups and no new safety concerns were identified. Conclusions These data support the concomitant administration of MenACYW-TT with 9vHPV and Tdap-IPV vaccines in adolescents. Trial Registrations Clinicaltrials.gov, NCT04490018; EudraCT: 2020-001665-37; WHO: U1111-1249-2973.